2017
DOI: 10.3892/mco.2017.1165
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of CD168 correlate with the stage and grade of squamous cell carcinoma of head and neck

Abstract: Abstract. The receptor for hyaluronan-mediated motility CD168 is associated with the processes of oncogenesis and metastasis. The objective of the present study was to determine the possible association between the expression and distribution of CD168 and the tumor stage of head-and-neck squamous cell carcinoma (SCC). Formalin-fixed and paraffinembedded tumor samples obtained from 100 patients during primary resection of SCC from the oral cavity, oropharynx, hypopharynx or larynx were included in the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, when cardiomyocytes are exposed to oxygen, expression of HMMR is decreased significantly (21,22). HMMR is overexpressed in numerous types of tumor, including breast, bladder and endometrial cancer (14)(15)(16)(17), and knockdown of HMMR inhibits the growth of tumor cells (23,24). However, the specific molecular regulatory mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when cardiomyocytes are exposed to oxygen, expression of HMMR is decreased significantly (21,22). HMMR is overexpressed in numerous types of tumor, including breast, bladder and endometrial cancer (14)(15)(16)(17), and knockdown of HMMR inhibits the growth of tumor cells (23,24). However, the specific molecular regulatory mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…All these biological characteristics are associated with the occurrence, development and metastasis of tumors. In clinical studies, HMMR has been shown to be expressed in malignant glioma, as well as breast, bladder and endometrial cancer (14)(15)(16)(17). The HMMR gene is highly expressed in mouse embryonic cardiomyocytes and regulates cell cycle as a mitotic regulator (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no valuable immuno-histochemical biomarkers predicting the clinical outcomes of head-and-neck SCC have been described. [18] This led researchers to study factors that could predict the prognosis. These factors may help personalized therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, knockdown of CD168 reduces the holoclone‐forming ability of CSCs (Shigeishi et al., 2013). At present, the expression patterns of CD168 in OSCC have been determined in a few studies (Johrens et al., 2017; Schmitt et al., 2009; Shigeishi et al., 2009; Yamano et al., 2008), but due to the short observation times and small patient cohorts, the correlation between CD168 expression and patient prognosis in OSCC has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%